Non-canonical RNA polyadenylation polymerase FAM46C is essential for fastening sperm head and flagellum in mice†. Issue 6 (14th May 2019) - Zheng, Chunwei; Ouyang, Ying-Chun; Jiang, Binjie; Lin, Xiwen; Chen, Jian; Dong, Ming-Zhe; Zhuang, Xinjie; Yuan, Shuiqiao; Sun, Qing-Yuan; Han, Chunsheng
Abstract: Family with sequence similarity 46, member C (FAM46C) is a highly conserved non-canonical RNA polyadenylation polymerase that is abundantly expressed in human and mouse testes and is frequently mutated in patients with multiple myeloma. However, its physiological role remains largely unknown. In this study, we found that FAM46C is specifically localized to the manchette of spermatids in mouse testes, a transient microtubule-based structure mainly involved in nuclear shaping and intra-flagellar protein traffic. Gene knockout of FAM46C in mice resulted in male sterility, characterized by the production of headless spermatozoa in testes. Sperm heads were intermittently found in the epididymides of FAM46C knockout mice, but their fertilization ability was severely compromised based on the results of intracytoplasmic sperm injection assays. Interestingly, our RNA-sequencing analyses of FAM46C knockout testes revealed that mRNA levels of only nine genes were significantly altered compared to wild-type ones (q < 0.05). When considering alternate activities for FAM46C, in vitro assays demonstrated that FAM46C does not exhibit protein kinase or AMPylation activity against general substrates. Together, our data show that FAM46C in spermatids is a novel component in fastening the sperm head and flagellum. Abstract : Non-canonical RNA polyadenylation enzyme FAM46C is specifically expressed in the manchette of spermatids in mouse testes and plays an essential role in spermiogenesis by fastening the sperm head and tail together.